Study of Wind Power Plant for Alternative Energy in Vannamei Litopeneaus Shrimp Cultivation - Sapto Nisworo; Deria Pravitasari; Zulfikar Aji Kusworo; Ashari Ashari; Naseer A Khan (Journal of Renewable Energy, Electrical, and Computer Engineering, 2022)
The focus of this research is to utilize wind energy for power generation as an electric power service for shrimp farming in the Kulon Progo district of Yogyakarta. This is done in order to minimize the use of diesel fuel in daily operations to drive the aerator pump that produces air bubbles and needs lighting. The method used is to calculate the need for electrical power in 24 hours, plan the windmill according to the local average wind speed. Parameters for measuring the final result are net present cost (NPC), cost of energy (CoE), and payback period. The scenario is used by installing a wind power generator compared to a generator from a diesel engine. The results of the study with a wind power generation system capable of producing 41755,07kW/year of power with the NPC value having a more efficient economic value of Rp. 158,254,000.00, a more efficient CoE value of Rp. 477.41, and for a diesel power plant of Rp. 1,569,015,240.00 and CoE worth Rp5,867,45. The payback period for the scenario with wind power is 3 years and 9 months and and 15 years 7 months for the scenario with diesel power plants.